Association between dietary fiber intake and obesity in US adults: from NHANES 1999–2018 - Lai, Siran; Zeng, Yuning; Lin, Geer; Li, Yue; Lin, Zixian; Ouyang, Xueren (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have demonstrated that dietary fiber reduces the incidence of diabetes or hyperlipidemia, but it remains unclear how dietary fiber intake relates to obesity incidence.MethodsA total of 39,184 adults were obtained from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. Multifactorial logistic regression analysis and Cox regression analysis were used to investigate the correlation between dietary fiber intake and obesity. Restricted cubic spline (RCS) analyses were used to describe the dose–response correlation between dietary fiber intake and the incidence of obesity. The robustness of the results was enhanced by Kaplan–Meier survival analyses and subgroup analyses.ResultsAfter adjusting for confounders, dietary fiber intake in the quartile 4 (≥ 20.8 g/day) was linked with a 26% lower incidence of obesity than those in the quartile 1 [≤9.1 g/day; odds ratios (OR) = 0.74, 95% confidence interval (95% CI): 0.67–0.83, p < 0.0001]. Further study indicated that a heightened dietary fiber intake was linked with a 21% decrease in all-cause mortality in quartile 4 compared to quartile 1 [hazard ratio (HR) = 0.79, 95% CI: 0.65–0.96, p = 0.02]. The RCS analysis conspicuously showed a non-linear U-shaped association between dietary fiber intake and all-cause mortality (p < 0.05), with 26.3 g/day being the turning point. The HR curve for all-cause mortality initially decreased and then increased.ConclusionAdequate dietary fiber intake has a favorable effect on reducing the incidence of obesity events, and obese patients with high dietary fiber intake exhibit lower all-cause mortality.